The antagonist principle John Henry Newman and the paradox of personality - Poston, Lawrence (Victorian literature and culture series, 2014)
"Drawing on biographical, historical, literary, and theological scholarship, this book considers the alternating roles of aggression and self-effacement in Newman's own personality and writing"--